Neurodevelopmental outcomes following intravitreal bevacizumab injection in Japanese preterm infants with type 1 retinopathy of prematurity - Arima, Mitsuru (PLoS One, 2020)
PURPOSE: The purpose of this study was to evaluate neurodevelopmental outcomes in 18-month old (corrected age) preterm infants who received an intravitreal bevacizumab (IVB) injection for the treatment of type 1 retinopathy of prematurity (ROP). METHODS: In this ten-year retrospective study, we reviewed the medical records of patients who underwent ROP screening at Kyushu University Hospital. Among the patients who received IVB or laser photocoagulation (LPC) for the treatment of type 1 ROP, we included infants whose neurodevelopmental examination (the Kyoto Scale of Psychological Development [KSPD]) results at 18 months corrected age were available. Then, the effect of IVB on the developmental quotient (DQ) in each KSPD domain (Postural-Movement, Cognitive-Adaptive, or Language-Social domain) or the overall DQ was investigated by performing linear regression analysis. RESULTS: Out of the 513 patients reviewed, 53 were included in the study. IVB and LPC were performed for 14 and 39 patients, respectively. Administration of IVB was significantly associated with neurodevelopmental delay in the Language-Social domain (p = 0.01). The observed association remained even after adjusting for gestational age and birth weight (p = 0.03). CONCLUSIONS: Administration of IVB may introduce a risk of developmental impairment of interpersonal relationships, socializations, and/or verbal abilities of preterm children. We recommended that preterm infants who received IVB undergo a neurodevelopmental reassessment during their school years or in adulthood.